Modern design approach of faults (toggling faults, bridge faults and SAT) of reduced ordered binary decision diagram based on combo & sequential blocks - Kurada Veera Bhoga Vasantha Rayudu; Jahagirdar Jahagirdar; P Rao (Institute of Advanced Engineering and Science, 2020)
In this Research we are going to develop ROBDD (Reduced Ordered Binary Decision Diagram) designs to detect toggling faults, bridge faults and SAT (Stuck at Fault), Here we are going to develop sequential blocks using ROBDD and applying to the mux to detect stuck at faults and also connecting the combo & Sequential blocks to find the toggling faults by connecting or using automatic test pattern generator. In this research we are going to develop the bridges between the blocks of ROBDD designs and converting them to and or logic to find the bridge faults of the design. Finding bridge and toggle faults are more difficult in logic designs, here we use an advance technique to find the faults of the design by calculating the path delays of the individual blocks of the design. More concentrating on the path delays by using basic stuck at faults methods to refer the faults (toggling and bridge faults) at mux output. In our research the basic design modules are ROBDD circuit of both combinational and sequential blocks are designed and tested using Multiplexer and K-map Simplification Methods. The main purpose of the research to find the faults at all levels of all logic designs which involves in both combinational and sequential blocks of the design.